Analysis of Inclusive Education Policy Implementation in Developing Countries - Khoiriyah, Umi; Karwanto, Karwanto; Setyowati, Sri; Nursalim, Mochamad; Khamidi, Amrozi (LP. Ma'arif Janggan Magetan, 2024)
Inclusive education is a global movement that emerged in response to the exclusion of learners who are viewed as different by the education system. Countries that hold the consensus to implement inclusive education have structured their legislation to ensure the implementation of inclusive education. However, the practice in schools may not live up to the rhetoric. The purpose of this study is to describe policy implementation in some developing countries. This research focuses on the implementation of inclusive education policies in developing countries. Developing countries are considered to be lacking in implementing inclusive education policies. In addition, developing countries often adopt policies from developed countries that are not in accordance with the characteristics of their countries. This research uses a literature study of journals related to the implementation of inclusive education in developing countries. The results show that the state that holds the consensus in the implementation of inclusive education has guaranteed the implementation of inclusive education in the constitution. The implementation of inclusive education experiences several obstacles related to accessibility, lack of accompanying teachers, poor acceptance by school community members and less than optimal funding. Constitutionally, the state has guaranteed the implementation of inclusive education, but in its implementation there are still several challenges that result in the achievement of the objectives of organizing inclusive education is not optimal. Therefore, the government needs to be consistent in implementing inclusive education policies, so that the achievement of inclusive education goals can be achieved.